Estimation of Transformers Health Index Based on Condition Parameter Factor and Hidden Markov Model - Selva A.M.; Yahaya M.S.; Azis N.; Ab Kadir M.Z.A.; Jasni J.; Yang Ghazali Y.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric transformers; Health; Hidden Markov models; Nonlinear programming; Probability distributions; Quality control; Viterbi algorithm; Condition parameters; Dissolved gas analysis; Distribution transformer; Emission probabilities; Health indices; Non-linear optimization; Remaining useful lives; Transition probabilities; Parameter estimation